Dehydrated Maydis stigma Enhances Nutritional and Antioxidative Capacities of Butter Cookies - Wan Rosli, W. I.; Nurhanan, A.R. (2015)
Background: Maydis stigma is generally disposed after taking the cornlettes as vegetable. Objective: In the present study, Maydis stigma powder (MSP) was partially replaced with wheat flour at the levels of 5, 10 and 15% in cookies preparation. Nutritional compositions were measured using standard methods and instrumental texture properties were also determined. Polyphenol compounds of cookies was determined using High Performance Liquid Chromatography technique while antioxidative activities were performed using FRAP and DPPH methods. Results: The incorporation of MSP in cookies increase the amount of protein, dietary fiber and ash content compared to cookie prepared from wheat flour (control). The present study also demonstrated that considerable higher polyphenol content (60.4% to 86.8%) and antioxidative improvement has attained by incorporation of MSP in cookie formulations. The MSP-based cookies have stronger free radical scavenging capacity (24.45 % to 62.73%) and ferric reducing capacity (16.94 to 342.00 μmol TE/g) with higher gallic acid and ferulic acid compound compared to all-wheat based cookies. Conclusion: Cookies with high antioxidative capacities can be prepared by replacing wheat flour with MSP up to 10%. Thus, MSP is suggested as potential nutritional and natural antioxidant sources for processed food products.